Pengaturan Kecepatan Motor Induksi Tiga Fasa Menggunakan Spwm Inverter dan Kontrol Pid dengan Metode Hibrid Volt/Herzt Konstan-Sensor Arus - Ramly Rasyid; Miftah Muhammad; Rahman R. Rasyid (Program Studi Teknik Elektro Universitas Khairun, 2022)
Three-phase induction motors are often used in every industry because three-phase induction motors are relatively cheap. On the three-phase induction motor in order to get a varied speed, one of the methods is the Three-Phase Induction Motor Speed Setting Using SPWM Inverter And Hybrid Volt/Herzt Constant-Sensor Current-Density PID Control in order to maintain the speed of the motor. This simulation was carried out with Matlab 2007 software. Induction motor speed performance set with a set point of 100 rad/detm 140 rad/sec, and 200 rad.det is a consecutive rise time of 0.002 seconds, 0.00116 seconds, and 0.006 seconds, a maximum overshoot of 5.4%, 1.25%, and 0.875% respectively and 0.1518 seconds, 0.1464 seconds, and 0.15 seconds respectively. The response torkanya values between 75 Nm, 90 Nm, and 100 Nm respectively, while the performance of the insulated current is very small